PERAN EKUITAS MERK TERHADAP LOYALITAS MERK BARBERSHOP DI KOTA YOGYAKARTA - Budi Setyanta (UNIVERSITAS PGRI MADIUN, 2018)
ABSTRACTThis study aims to identify the role of brand equity on brand loyalty in the barbershop. 200 samples were collected using questionnaires to test multiple linear regression using SPSS tool. The results of this study indicate that the dimension of brand equity has a positive and significant effect on brand loyalty barbershop. Further research is needed to test the model of this study to examine the model's generalisation capabilities.Keywords: Brand Loyalty, Brand Equity